FENOMENA INDO-PASIFIK DAN DIPLOMASI INDONESIA - Sinta Herindrasti (Kajian Asia Pasifik, 2019)
The emergence of the Indo-Pacific terminology since 2007 until 2013, which is still growing stronger up until now, has created a new â€œtensionâ€ dynamic among various actors in the region. The term Indo-Pacific at least reflects the exisiting new geopolitics transformation discourse in the regions between Indian and Pacific Oceans. With its strategic position, Indonesia is also active in the development of Indo-Pacificâ€™s discourse and diplomacy. Considering the broad geographical area coverage of the Indo-Pacific concept and various state-actors including involvement of their power distribution and structure, comprehensive and critical analysis of Indo-Pacific phenomenon observation are therefore required. What is the purpose of Indonesia through its Indo-Pacific diplomatic action? Are there any current urgent needs which warrant involvement in these broad geopolitical issues? Does Indo-Pacific answer the needs of Indonesia and ASEAN in the middle of their various multilateral agendas? This paper would like to elaborate on the importance of Indonesiaâ€™s or ASEANâ€™s involvement in the Indo-Pacific by considering real situations, real needs and obstacles to be faced, especially in regards to politics-security challenges. Keywords: Indo-Pacific Phenomenon, Indonesia Diplomacy Abstrak Kemunculan terminologi Indo-Pasifik sejak tahun 2007 hingga 2013 yang menguat hingga sekarang telah menciptakan dinamika â€œketeganganâ€ baru antar berbagai aktor kawasan. Istilah Indo-Pasifik setidaknya mencerminkan adanya diskursus transformasi geopolitik baru di kawasan antara lautan Hindia dan Pasifik tersebut. Tidak ketinggalan Indonesia dengan posisi strategisnya juga terlibat aktif dalam pengembangan diskursus dan diplomasi Indo-Pasifik. Menimbang luasnya cakupan area geografis konsep Indo-Pasifik dan banyaknya aktor negara termasuk distribusi power dan struktur yang akan terlibat, maka diperlukan analisis komprehensif kritis dalam melihat fenomena Indo-Pasifik. Apa sebenarnya tujuan Indonesia melalui aksi diplomasi Indo-Pasifik? Apakah ada kebutuhan yang sangat mendesak saat ini untuk terlibat dalam isu geopolitik yang sangat luas ini? Apakah Indo-Pasifik menjawab kebutuhan Indonesia dan ASEAN di tengah agenda multilateral yang sudah sedemikian banyak? Paper ini ingin melihat urgensi keterlibatan Indonesia/ASEAN dalam Indo-Pasifik dengan mempertimbangkan situasi dan kebutuhan nyata serta kendala yang akan dihadapi terutama terkait tantangan dimensi politik-keamanan (security). Kata Kunci: Fenomena Indo-Pasifik, Diplomasi Indonesia